Effects of strontium ions on the proliferation and mineralization of human fetal mesenchymal stem cells. - Lim, Xin Ying. (2013)
Strontium ranelate, a drug used for the treatment of osteoporosis has been shown to aid in bone formation and decrease bone resorption. This study was done with the aim of determining the effect of varying concentration of strontium ions on the mineralization and proliferation of human fetal mesenchymal stem cells (hfMSCs) under 2D and 3D environment. Supplementation of strontium ions in culture media resulted in higher mineralization (9.57X and 4.55X for the 2.0mM and 3.0mM strontium groups respectively, p<0.05) of hfMSCs as compared to the control (osteogenic medium only) in a short- term 2D culture of 7 days. In long- term 2D culture of 14 days, the absence of dexamethasone in the osteogenic medium generated greater mineralization (9.05X, at day 14, p<0.05) as compared to control (osteogenic medium alone) under the influence of 2.0mM strontium ions. Also, strontium ions favor the proliferation of hfMSCs at 14 days culture (1.6X and 1.86X for the 0.5mM and 1.0mM strontium group respectively vs. control, p<0.05). In a 3D environment using two different conformations of polycaprolactone-tricalcium phosphate (PCL-TCP) scaffold, it was found to provide a more favorable environment for the mineralization of hfMSCs as compared to 2D culture under the influence of 0.5mM strontium ions (10.2X higher for 3D scaffold cube and